Inhibition of Return in Visual Search Does Not Rely on Spatial Working Memory - Höfler, Margit (Adv Cogn Psychol, 2022)
Inhibition of return (IOR) prevents the immediate reorientation to previously attended locations, such that unattended locations are prioritized. In the current study, we were interested in whether saccadic IOR is affected by the storage of visuospatial information in working memory (WM) during a visual search task. To this end, participants searched a display for a target letter once while holding no, two, or four object locations in their spatial WM. During the search, either a previously inspected or an uninspected item was probed, and the participants were instructed to immediately saccade to this probed item before resuming the search. The results showed that saccadic latencies to previously inspected items were longer than to uninspected items, indicating the presence of IOR during the search. However, this effect was observed regardless of the number of item locations held in the spatial WM. This finding suggests that saccadic IOR does not rely on visuospatial WM in visual search.